Sequelae of Cerebral White Matter Injury - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
Diffusion tensor MRI was used to evaluate the effects of cerebral white matter (WM) injury on subsequent microstructural brain development in 20 premature infants studied at Children's Hospital, Harvard Medical School, Boston, MA.